2011
DOI: 10.1177/1934578x1100601234
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Cytotoxic Effects of Mexican Medicinal Plants

Abstract: The antimicrobial effects of the Mexican medicinal plants Guazuma ulmifolia, Justicia spicigera, Opuntia joconostle, O. leucotricha, Parkinsonia aculeata, Phoradendron longifolium, P. serotinum, Psittacanthus calyculatus, Tecoma stans and Teucrium cubense were tested against several human multi-drug resistant pathogens, including three Gram (+) and five Gram (-) bacterial species and three fungal species using the disk-diffusion assay. The cytotoxicity of plant extracts on human cancer cell lines and human nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 9 publications
2
35
0
3
Order By: Relevance
“…Spleen is involved in fighting the systemic infections, whereas NK cells play a critical role in immune surveillance by the secretion of cytokines such as IFN-␥ (Randy and Venkataraman, 2002). Previously, we showed that Justicia spicigera ethanol extracts tested at 100 g/ml stimulated the proliferation of human peripheral blood mononuclear cells with similar potency as compared to phytohemagglutinin 1 g/ml (Jacobo-Salcedo et al, 2011). In this study, we showed that Justicia spicigera stimulates the phagocytosis, NO production and H 2 O 2 release with higher potency than LPS in human differentiated macrophages.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Spleen is involved in fighting the systemic infections, whereas NK cells play a critical role in immune surveillance by the secretion of cytokines such as IFN-␥ (Randy and Venkataraman, 2002). Previously, we showed that Justicia spicigera ethanol extracts tested at 100 g/ml stimulated the proliferation of human peripheral blood mononuclear cells with similar potency as compared to phytohemagglutinin 1 g/ml (Jacobo-Salcedo et al, 2011). In this study, we showed that Justicia spicigera stimulates the phagocytosis, NO production and H 2 O 2 release with higher potency than LPS in human differentiated macrophages.…”
Section: Discussionmentioning
confidence: 60%
“…Previously, we showed that Justicia spicigera showed strong cytotoxic effects against HeLa cells (Jacobo-Salcedo et al, 2011). In this study, we showed that JSE exerted cytotoxic effects and induced 35% apoptosis in HeLa cells, compared to untreated cells.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations